2017
DOI: 10.1039/c6fd00232c
|View full text |Cite
|
Sign up to set email alerts
|

Strain–capacitance relationship in polymer actuators based on single-walled carbon nanotubes and ionic liquid gels

Abstract: We investigate the electromechanical properties of bucky-gel electrochemical actuators incorporating various amounts of single-walled carbon nanotubes and an ionic liquid electrolyte, 1-butyl-3-methylimidazolium tetrafluoroborate, that are able to convert electrochemical energy into mechanical energy. The interplay between mechanical and electrochemical effects is studied. The electromechanical responses are investigated by means of electrochemical impedance spectroscopy and bending displacement measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Therefore, it is thought that when the electrode films of the EAP actuator were made of nanofiber, the surface area of the electrode films of the EAP actuator increased and then the capacitance of the EAP actuator increased. 30) Although the nanofiber electrode film has a surface area about 100 times that of the cast electrode film in Fig. 5, the capacitance did not become 100 times larger.…”
Section: Capacitance Of the Actuatorsmentioning
confidence: 83%
“…Therefore, it is thought that when the electrode films of the EAP actuator were made of nanofiber, the surface area of the electrode films of the EAP actuator increased and then the capacitance of the EAP actuator increased. 30) Although the nanofiber electrode film has a surface area about 100 times that of the cast electrode film in Fig. 5, the capacitance did not become 100 times larger.…”
Section: Capacitance Of the Actuatorsmentioning
confidence: 83%
“…Because SWCNTs appeared to be the least emissive in [C 4 -mim]­BF 4 , which is a widely used IL in conjunction with SWCNTs, ,, we explored pathways for enhancing the emission of SWCNTs in this IL (Figure ). We found that by increasing the amount of water in [C 4 -mim]­BF 4 , the emission intensity of SWCNTs was completely restored.…”
mentioning
confidence: 99%